(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This article is a comprehensive literature review that examines the current understanding of Consumer Purchase Behavior. The goal is to trace the development of the key ideas in these fields over 124 years. A total of 1,000 publication records were obtained from Google Scholar and Scopus using keyword search. These data yielded almost 1,676,475 citations. The research conducted bibliometric analysis using these records Moreover, the number of citations on both subjects has increased by more than 2.5 times in the last two decades and is projected to double in the future decades. This study also provides suggestions for further research.